(untitled) (Semiárida, 2020)
In an area of shrublands in the southwest of La Pampa we determined woody aerial phytomass and density of shrubs. The results obtained in the area I (Aquatic), II (amphibiam) and III (rarely inundated) were 11.000, 12.000 and 13.000 k/ha respectively. Density of Larrea cuneifolia were 979, 1.686 and 1.736 pI /ha in the areas I, II y III. Atriplex lampa had 670. 1079 and 933 pI/ha. Larrea divaricata had 357, 894 and 913 pl/ ha in the threee different areas. The principal units of vegetation were: a shrubland of Larrea cuneifolia, a shrubland of Larrea divaricata and a Heathland of Suaeda divaricata and Atriplex ondulata. A tall grassland of Cortadera selloana was present on the sandy soils.